Penerapan Praktik Lean Service Melalui Value Stream Mapping padaDepartemen Food and Beverage Service Hotel X - Langit, Putri Sangga; Insanita, Rizqiah (Jurnal Manajemen dan Usahawan Indonesia, 2022)
The development of the hospitality industry in Indonesia increasingly pushes the hotel business to provide the best service for hotel guests. As one of the most affected by customer satisfaction, the Food and Beverage Service (FBS) department of every hotel needs to provide the most effective and efficient services. The study which held at Hotel X is purposed to identify and eliminate wastes in the room service breakfast set process at Hotel X using the value stream mapping method in order to attain effectivity and efficacy in services. In addition, this study also provides suggestions for improvement to attain the elimination of waste. The result of this research is the identification of four wastes, including over-processing, motion, defects, and waiting. The suggested improvements are including updating the ordering system, recruiting hygiene specialist, conducting walkthrough inspections, using inventory management technology, performing maintenance on room service delivery equipment, and building linen and garbage chutes. Based on this study’s future state map, the increases in the parameters in the entire value stream is obtained, namely the total lead time decreased by 43%, the total process time decreased by 42%, the total non-value added time decreased by 51%, and the total waiting time decreased by 44%. This study suggests that the proposed improvements are implemented by Hotel X.